Internalisasi Nilai-Nilai Multikultural dalam Mengembangkan Sikap Moderasi Beragama (Studi Kasus di PMD. Gontor Ponorogo) - El-Yunusi, Muhammad Yusron Maulana (Proceedings of Annual Conference for Muslim Scholars, 2022)
The existence of many kinds of cultures, also its cases have happened, there is an influence towards educational systems. Even, they are able to link or cooperate. Then, the multi cultural education gives awareness that the differences. Some researchers have chosen a Islamic boarding school, GONTOR as a researching object because it has a good receiver of acceptance background. The main aim of that research is to comprehend the moderation and the internal values of cultures which developed. This research is qualitative. Technically, data collection has been done by observation, interview and documentation. The values of multi cultures which developed by PMD Gontor in forming the attitudes of religious moderation on Santri (students) consist of The Five Values, PMDG also develops a motto. The modern values implementated in teaching, forming 'pesantren' culture as well as extra and intra curricula.